FEATURES OF SYSTEMIC IMMUNITY IN PATIENTS WITH A PRIMARY “DRY EYE” SYNDROME - N. N. Ratkina; O. F. Lykova; O. Y. Baturina; O. A. Klitsenko (Медицинская иммунология, 2014)
Fifty patients with primary "dry eye" syndrome underwent examination of systemic immunity including the determination of cell populations and subsets of CD3+, CD4+, CD8+, CD16+, CD20+ lymphocytes; measurements of major immunoglobulins: IgA, IgM, IgG; circulatory immune complexes (CIC); rheumatoid factor, antibodies to denatured and nondenatured DNA, and phagocytic index. When compared to relatively healthy subjects (n = 30), the patients, showed decreased contents of CD3+ and CD4+T-lymphocytes, increased IgM and CIC concentrations, along with presence of autoantibodies in blood. Moreover, some variable changes were revealed in the quantities of CD8+ cytotoxic T-lymphocytes, and the values of immunoregulatory index (IRI). As based on immunologic findings, with regard of CIC contents, autoantibody titers and IRI values, we have discerned four types of primary "dry eye" syndrome, i.e., simple, cytotoxic, CIC-positive, and Sjogren's syndrome. The changes of systemic immunity in the patients with different etiology of primary "dry eye" syndrome should be considered when elaborating therapeutic strategies and aiming for prophylaxis of immunologic disorders in such a cohort of patients.